2021
DOI: 10.3390/catal11020226
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Properties of Metal-Free Catalysts for the Highly Efficient Desulfurization of Sour Gases under Harsh Conditions

Abstract: Carbon-based nanomaterials, particularly in the form of N-doped networks, are receiving the attention of the catalysis community as effective metal-free systems for a relatively wide range of industrially relevant transformations. Among them, they have drawn attention as highly valuable and durable catalysts for the selective hydrogen sulfide oxidation to elemental sulfur in the treatment of natural gas. In this contribution, we report the outstanding performance of N-C/SiC based composites obtained by the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Pham-Huu et al have widely demonstrated the importance of SiC structures as inert and thermally stable supports for a C–N active phase to be employed in the selective H 2 S oxidation to elemental sulfur in sour gas tails. Although SiC matrices mainly hold the role of refractory carriers for porous carbon networks in the form of N-doped systems as the active phase, they play a fundamental role in the catalyst shaping according to its downstream application. In particular, these authors have demonstrated the advantages of SiCs for the preparation of robust and durable hybrid organic–inorganic composites obtained from growing C deposits at the SiC surface both in the form of N-doped carbon nanotubes (N-CNTs) (Figure left) or porous N-doped C networks obtained from the CVD technique or the metal-free thermal treatment of selected C- and N-source building blocks, respectively.…”
Section: Sic and Its Composites As Metal-free Catalystsmentioning
confidence: 99%
“…Pham-Huu et al have widely demonstrated the importance of SiC structures as inert and thermally stable supports for a C–N active phase to be employed in the selective H 2 S oxidation to elemental sulfur in sour gas tails. Although SiC matrices mainly hold the role of refractory carriers for porous carbon networks in the form of N-doped systems as the active phase, they play a fundamental role in the catalyst shaping according to its downstream application. In particular, these authors have demonstrated the advantages of SiCs for the preparation of robust and durable hybrid organic–inorganic composites obtained from growing C deposits at the SiC surface both in the form of N-doped carbon nanotubes (N-CNTs) (Figure left) or porous N-doped C networks obtained from the CVD technique or the metal-free thermal treatment of selected C- and N-source building blocks, respectively.…”
Section: Sic and Its Composites As Metal-free Catalystsmentioning
confidence: 99%
“…The desulfurization of sour gases was studied by Duong-Viet et al in carbon-based nanomaterials in the form of N-doped networks by the coating of a ceramic SiC. The chemical and morphological properties of the nano-doped carbon phase/SiC-based composite were controlled to get more effective and robust catalysts able to remove H 2 S from sour gases under severe desulfurization conditions such as high GHSVs and concentrations of aromatics as sour gas stream contaminants [7].…”
Section: Special Issuementioning
confidence: 99%
“…We have recently described an effective and general strategy to the production of highly metal loaded and atomically dispersed Fe-based composites as performing electrocatalysts for the oxygen reduction reaction, starting from cheap and food-grade raw components in combination with key thermo-chemical etching/doping phases (NH 3 atmosphere). 27 The employed methodology took advantage from a proprietary synthetic procedure originally applied to the preparation of N-enriched mesoporous carbon-based 1D-3D networks [36][37][38] or organic-inorganic composites [39][40][41] to be employed as metal-free catalysts for a wide series of industrially relevant transformations. Accordingly, Fe-SAs were prepared from D-glucose (C 6 H 12 O 6 ) as the main C-source, ammonium carbonate [(NH 4 ) 2 CO 3 ] as N-source and citric acid (C 6 H 8 O 7 ) as a sacrificial carrier for Fe 3+ and NH 4 + ions.…”
Section: Introductionmentioning
confidence: 99%